An Observational Study to Identify the Role of Online Communication in Offline Social Networks - Ali, Mona A. S.; Hassanien, Aboul Ella (Advanced Machine Learning Technologies and Applications, 2014)
Social networks are frequently categorized as online (supported electronically without necessitating participants meeting) or offline (defined though physical interactions). Often these social networks are treated as mutually exclusive but in many situations they coexist across the same community. In these circumstances online social networks provide communication to enhance information flow and support different types of relationship. In this paper we undertake an observational study of a social network of 98 undergraduate students to determine the role of on-line communication in offline social networks. We exploit social network analysis to examine the structure of the underlying communication. We examine the role of electronic social networks (web-based, email, telephone and SMS) to establish how different methods of communication and communication frequency support different types of relationship. Interesting trends emerge on how different technologies are used. The results reaffirm the importance of on-line social networks in facilitating structurally important weak links and reinforcing strong links.